1981
DOI: 10.1080/00288233.1981.10420867
|View full text |Cite
|
Sign up to set email alerts
|

The response to phosphorus of white clover and lotus inoculated with rhizobia or given KNO3

Abstract: White clover and lotus were grown in a controlled environment at P levels of 50, 500, and 1500 ppm and either inoculated with rhizobia (Ni) or given KN03 (N03). Na plants of lotus and white clover had different responses to P. The response of N03 plants to P was the same in both species. This implies that the reason(s) for the difference in response between Na plants lie in differences in the structure and function of the symbiotic association. Lotus plants had a greater proportion of plant dry weight, P, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…At high P levels, NIP ratio declined suggesting that N supply from fixation could not keep pace with P uptake. Hart et al (1981) similarly found that white clover growth response to P was reduced at high P levels when plants relied on fixed N compared to nitrate-N. At high levels of P supply, growth of N-fixing plants can be limited by N. Thus as level of P sup- ply increased, the relationship between leaf %N and total shoot P (and hence large plants) became negative, and between leaf %N and NIP ratio became positive (Table 3). Plant characters that were positively correlated with the linear P response coefficient and negatively correlated with the quadratic P response coefficient were those that had high values for highly P-responsive genotypes and low values for less P-responsive genotypes (Table 4).…”
Section: Comparison Of High and Low Phosphorus Response Groupsmentioning
confidence: 75%
See 1 more Smart Citation
“…At high P levels, NIP ratio declined suggesting that N supply from fixation could not keep pace with P uptake. Hart et al (1981) similarly found that white clover growth response to P was reduced at high P levels when plants relied on fixed N compared to nitrate-N. At high levels of P supply, growth of N-fixing plants can be limited by N. Thus as level of P sup- ply increased, the relationship between leaf %N and total shoot P (and hence large plants) became negative, and between leaf %N and NIP ratio became positive (Table 3). Plant characters that were positively correlated with the linear P response coefficient and negatively correlated with the quadratic P response coefficient were those that had high values for highly P-responsive genotypes and low values for less P-responsive genotypes (Table 4).…”
Section: Comparison Of High and Low Phosphorus Response Groupsmentioning
confidence: 75%
“…This suggests that P response differences might be related to differences in symbiotic effectiveness of genotypes and associated rhizobia, differences in the partitioning of P by the plant as a result of nodulation, or differences in acquisition of fixed N, its transport and utilisation for growth. Hart et al (1981) found that differences in P response between white clover and lotus were greater when grown with N supplied by N fixation than as nitrate. They concluded that the difference in P response between the two species is possibly related to the structure and functioning of the symbiotic association.…”
Section: Comparison Of High and Low Phosphorus Response Groupsmentioning
confidence: 93%
“…This is clearly confirmed by our present investigation. The importance of phosphate in the nutrition of nodulated legumes to improve their growth, yields and N2-fixation has been well documented (Gupta & Sen 1966;Idris et al 1977aIdris et al , b, 1978Gates 1974;Cassman et al 1981;Hart et al 1981;Taha et al 1967;Subba Rao 1976).…”
Section: Resultsmentioning
confidence: 95%
“…The higher phosphorus concentration in root tissues of trefoil (Fig. 2) may be causally related to its lower yields as phosphorus in nodules becomes unavailable for metabolism elsewhere (Hart 1982). Although phosphorus sequestration by nodules prevents the translocation of internal nutrient reserves to active growing points as was suggested by Koide ( 1991 ), this process guarantees establishment success of trefoil.…”
Section: Discussionmentioning
confidence: 99%
“…Although trefoil plants grew less than tall fescue, the presence of active root nodules in all plants at the entire range of P supply may have resulted in an additional demand. Phosphorus concentration in nodules (up to 45% of root phosphorus) is required by ATP for nitrogen fixation (Hart 1982). Such a sink is absent in fescue plants, which are totally reliant on soil mineral nitrogen.…”
Section: Discussionmentioning
confidence: 99%